URGENSI PEMIKIRAN PENDIDIKAN MUHAMMAD IQBAL DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM ANAK USIA DINI - Muhibbin (Qiro'ah : Jurnal Pendidikan Agama Islam, 2023)
This paper seeks to explore how the contribution of educational thought Muhammad Iqbal inlearning Islamic Religious Education in early childhood. This type of research is included inlibrary research. The data analysis method used in this study is descriptive analysis. Thisstudy concluded that the thoughts of Muhammad iqbal about the basic principles in theimplementation of education that can be widely understood and can be applied, especially inIslamic Religious Education Early Childhood Learning that can be used to form the conceptindividualita, individualita growth, physical and spiritual harmony, individuals and society,creative evolution, the role of intellect and intuition, Character Education, Social.